2020
DOI: 10.3390/molecules25163602
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Cryptotanshinone in a Direct Reprogramming Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a well-known age-related neurodegenerative disease. Considering the vital importance of disease modeling based on reprogramming technology, we adopted direct reprogramming to human-induced neuronal progenitor cells (hiNPCs) for in vitro assessment of potential therapeutics. In this study, we investigated the neuroprotective effects of cryptotanshinone (CTN), which has been reported to have antioxidant properties, through PD patient-derived hiNPCs (PD-iNPCs) model with induced oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Tanshinone IIA, a major component of Salvia miltiorrhiza Bge, has been shown to elevate TH protein levels and suppress caspase-3 expression in SNpc, thereby protecting DA neurons (Tian et al, 2018). It has been shown that cryptotanshinone, from Salvia miltiorrhiza Bge, significantly suppresses apoptosis by restoring mitochondrial functions in PD patient-derived hiNPCs (Lee et al, 2018). The other identified active ingredients include paeoniflorin, isorhynchophylline and verbascoside, which were from Paeonia lactiflora Pall, Uncis Uncaria rhynchophylla (Miq.)…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA, a major component of Salvia miltiorrhiza Bge, has been shown to elevate TH protein levels and suppress caspase-3 expression in SNpc, thereby protecting DA neurons (Tian et al, 2018). It has been shown that cryptotanshinone, from Salvia miltiorrhiza Bge, significantly suppresses apoptosis by restoring mitochondrial functions in PD patient-derived hiNPCs (Lee et al, 2018). The other identified active ingredients include paeoniflorin, isorhynchophylline and verbascoside, which were from Paeonia lactiflora Pall, Uncis Uncaria rhynchophylla (Miq.)…”
Section: Discussionmentioning
confidence: 99%
“…Cells regulate the occurrence of various oxidative stress injuries through the Nrf2 signaling pathway ( Ben-Yehuda Greenwald et al, 2017 ). CTS has been found to exert various protective effects by activating the intracellular Nrf2 signaling pathway, such as alleviating ethanol-induced liver injury ( Nagappan et al, 2019 ), regulating the endotoxin-induced inflammatory response of microglia ( Zhou et al, 2019 ), and inhibiting the MG132-induced apoptosis ( Lee et al, 2020 ). Since CTS could effectively inhibit UV radiation-induced ROS production in HaCaT and HFF-1 cells, we speculated that it may also inhibit oxidative damage to the skin cells induced by UV radiation through the Nrf2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…CTS can inhibit the apoptosis of Parkinson’s disease patient-derived human-induced neuronal progenitor cells (PD-hiNPCs) by restoring the membrane potential availability in PD-hiNPCs, reducing the levels of total ROS and mitochondrial ROS, and down-regulating the expression of apoptotic protein caspase-3 ( Lee et al, 2020 ). ROS have been recognized as an important factor in Parkinson’s disease ( Hemmati-Dinarvand et al, 2019 ).…”
Section: Cts and Neural Stem/progenitor Cellsmentioning
confidence: 99%
“…CTS can exert antioxidant effects by activating the transcription of nuclear factor erythroid 2-related factor 2 (NRF2) signaling pathway ( Figure 4 ). Among them, CTS can boost the expression of certain genes, such as superoxide dismutase 1 (SOD1), peroxiredoxin 1 (PRX1), peroxiredoxin 5 (PRX5), glutathione peroxidase (GPX1) and NAD(P)H quinone dehydrogenase 1 (NQO1) in PD-hiNPCs ( Lee et al, 2020 ). These results provide evidence for CTS as a treatment for PD.…”
Section: Cts and Neural Stem/progenitor Cellsmentioning
confidence: 99%